Perceptions of professionals interested in accounting and auditing about acceptance and adaptation of global financial reporting standards - Orhan Bozkurt; Mehmet İslamoğlu; Yaşar Öz (Journal of Economics, Finance and Administrative Science, 2013)
Nowadays, one of the final aims of the institutions working on transparency and standardization of financial statements, and the publication of standards related to the profession of accounting & auditing has been to put into practice a uniform global set of standards which will be applicable in finance. Before 2000, in the case of a preference between IFRS & US GAAP regarding which should be internationally accepted uniform set of application, world public opinion used to accept U.S. Generally Accepted Accounting Principles (US GAAP) as reference. Today, great majority of the world takes IFRS as a reference. This study contains evaluations related to the results of research on the thoughts & perceptions of the professionals interested in accounting and auditing about application and development of international financial reporting standards as national financial reporting standards. As a result of the research, it was determined that those interested in accounting and auditing see significant advantages in the application of IFRS. Accountants and auditors think that in case IFRS is applied, comprehensibility and reliability of financial statements shall increase, at the same time accounting frauds shall decrease. – – Hoy en día, uno de los objetivos finales de las instituciones que trabajan por la transparencia y la estandarización de los estados financieros y por la publicación de normas relacionadas con la profesión de la contabilidad y la auditoría ha sido poner en práctica un conjunto de normas internacionales uniformizadas que se aplicarán en el mundo financiero. Antes de 2000, cuando había que elegir entre las NIIF y los GAAP estadounidenses como conjunto uniforme, aceptado y de aplicación internacional, la opinión pública mundial tendía a admitir los principios estadounidenses de contabilidad generalmente aceptados (US GAAP) como referencia. Actualmente, en la mayoría de los lugares se toman como referencia las NIIF. En este estudio se incluyen evaluaciones relacionadas con los resultados de la investigación acerca de los pensamientos y las percepciones de los profesionales interesados en contabilidad y auditoría sobre la aplicación y el desarrollo de normas internacionales de información financiera como normas de información financiera nacionales. Como resultado de la investigación, se concluyó que las personas interesadas en contabilidad y auditoría observaron ventajas significativas en la aplicación de las NIIF. Los contables y auditores creen que, si se aplican las NIIF, aumentará la inteligibilidad y la fiabilidad de los estados financieros y, a su vez, se reducirán los fraudes contables.
Keywords: M40; M41; M42; 330; International Financial Reporting Standards; Turkish Accounting Standards; Benefit; Interpretation; Perceptions of Standards; Responsibility; Advantage of Application of International Financial Reporting Standards; Normas internacionales de información financiera; Normas turcas de contabilidad; Beneficio; Interpretación; Percepciones de normas; Responsabilidad; Ventaja de aplicación de normas internacionales de información financiera